1997
DOI: 10.1021/np960693q
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigation of Resin Glycosides from Ipomoea lonchophylla

Abstract: A fraction from Ipomoea lonchophylla, which was toxic to mice, contained an inseparable mixture of resin glycosides with differing numbers of C5 ester groups on the hexasaccharide chain. After alkaline hydrolysis of the esters, the structure of the major component (1) was elucidated using high-field NMR spectroscopy, mass spectrometry, chemical studies, and comparison with known resin glycosides. Compound 1 was identified as 3,11-dihydroxytetradecanoic acid 11-O-beta-quinovopyranosyl-(1-->2)-beta-glucopyranosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…One fraction from I. lonchophylla was toxic to mice but no tests have so far been carried out to determine whether this toxic fraction contribute to intoxication and death among newly born lambs. The toxic fraction contained an inseparable mixture of resin glycosides (Macleod et al, 1997).…”
Section: Ipomoea Lonchophylla Jm Blackmentioning
confidence: 99%
“…One fraction from I. lonchophylla was toxic to mice but no tests have so far been carried out to determine whether this toxic fraction contribute to intoxication and death among newly born lambs. The toxic fraction contained an inseparable mixture of resin glycosides (Macleod et al, 1997).…”
Section: Ipomoea Lonchophylla Jm Blackmentioning
confidence: 99%
“…This plant is used in Portuguese traditional medicine to cure hydropsy, paralysis, rheumatism, and scurvy [77]. (81) has been isolated from the aerial parts of Australian plant Ipomoea lonchophylla [78]. Many species of Ipomoea were and still are used in folk medicine in different parts of the world [79].…”
Section: Formation Of Fatty Acid Glucuronides 16 ± 18 In Human Livermentioning
confidence: 99%
“…Ipomoea imperati (Vahl) Griseb., Convolvulaceae, is used in traditional medicine for the treatment of infl ammation, swelling and wounds, as well as to treat pains after childbirth and for stomach problems (Fosberg & Sachet, 1977). Pharmacological studies on extracts of many species of Ipomoea have reported anti-infl ammatory, antimicrobial, analgesic, spasmogenic, anti-spasmolytic, hypotensive, psychotomimetic and anticancer effects (MacLeod et al, 1997). Chemical investigations have shown that indole alkaloids and resin glycosides are the most common biologically active constituents in the Convolvulaceae (Noda et al, 1994;Noda et al, 1998).…”
Section: Introductionmentioning
confidence: 99%